Theoretical investigation of a benzene-vanadium multiple-decked sandwich chain on a gold surface - Rahman, Md. Mamudur; Muhida, Rifki; Chowdhury, Md. Sazzad Hossien; Setiyanto, Henry; Zainuddin, Hishamuddin; Zakaria, Azmi; Kasai, Hideaki (American Scientific Publishers, 2012)
We investigate the formation and magnetic properties of benzene-vanadium multipledecked sandwich chain on Au(111) surface using first principles calculations based on density functional theory. We show that in the formation of the chain on the surface, each of the two hydrogen atoms of benzene bonds with only one gold atom, while the carbon and vanadium atoms do not contribute to bonding. We find that this system has no magnetic moment where two vanadium atoms are antiferromagnetically arranged, for which we suggest a superexchange interaction mechanism.